Task sharing in the eye care workforce: Screening, detection, and management of diabetic retinopathy in Pakistan. A case study. (11th March 2018) - Shah, Mufarriq; Noor, Ayesha; Deverell, Lil; Ormsby, Gail M.; Harper, C. Alex; Keeffe, Jill Elizabeth
Summary: Purpose: Diabetic retinopathy (DR) is a preventable cause of vision loss. Reducing vision loss due to DR and providing access to eye care services for people with diabetes have been severely constrained by a shortage in the number of ophthalmologists. This study aimed to explore the potential for task sharing in the eye care workforce for screening, detection, and management of DR. Methods: Using purposive sampling, 24 participants were recruited from four selected hospitals in 2 provinces in Pakistan. Face‐to‐face interviews were conducted to explore the potential for task sharing in DR management. Results: Amongst 24 participants recruited, 22 (91.7%) including administrators (n = 3), ophthalmologists (n = 10), optometrists (n = 3), mid‐level eye care workers (n = 4), and endocrinologist (2) participated in the study. All participants indicated the need for an organised screening program for DR detection through task sharing. Participants suggested that people with diabetes can be sent directly to an optometrist for initial eye exams, rather than making them wait to be examined by an ophthalmologist. Factors favouring task sharing included the name task sharing rather than task shifting and a high demand for eye care services. Major barriers to implementation of task sharing included the lack of a trained eye care workforce in the healthcare system and the lack of coordination amongst health professionals and policy makers. Conclusion: Participants were accepting task sharing approach and believed that task sharing could improve access to eye care services for people with diabetes and better utilise the services of eye and healthcare providers.